PENERAPAN STRATEGI JOYFUL LEARNING PADA MATA PELAJARAN PAI DI UPTD SMPN 1 KEC SULIKI KABUPATEN LIMA PULUH KOTA - Anisa Emiliza; Charles; Pendi Hasibuan; Alimir (KOLONI, 2022)
This research departs from the background of grade VII-2 students at UPTD SMPN 1 Suliki District, often being the object of blame when they are unable to absorb lessons. So that various predicates are always given to students, for example lazy, not paying attention to teacher explanations, naughty, stupid, and others. Even though it may be the cause of the inability of students to absorb the lessons given starting from an uninteresting and boring learning process. As a result, students become lazy and not interested in the material presented. Therefore, this study wants to dig deeper into how the implementation of the Joyful Learning Strategy in the Pie Subject Class VII-2 at UPTD SMPN 1 Suliki District. This research is a qualitative research with a descriptive qualitative approach. The focus of this research is Joyful Learning Strategy in Islamic Education Subject Class VII-2 at UPTD SMPN 1 KEC SULIKI. This study attempts to provide an overview of the implementation of the Joyful Learning Strategy in the Pie Subject Class VII-2 at UPTD SMPN 1 Suliki District. The primary sources of this research are observational data, interviews and documentation obtained from UPTD SMPN 1 Suliki District. The secondary sources are supporting data from related references. The results of this study indicate that in the application of joyful learning strategies in PAI subjects, the teacher conditions a pleasant learning atmosphere with interactive questions and answers, games, and memorizing learning materials by singing. not so optimal in implementing the joyful learning strategy, lack of awareness of students about the importance of learning. Students' enthusiasm for learning in participating in implementing the joyful learning strategy, lack of awareness of students about the importance of learning. Students' enthusiasm for learning in participating in learning is very low.  Keywords: Application of Joyful Learning Strategy.